2005
DOI: 10.2478/bf02476241
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidase from Penicillium canescens. Properties and immobilization

Abstract: β-galactosidase from Penicillium canescens was immobilized on chitosan, sepharose-4B, foamable polyurethane and some other carriers. The highest yield of immobilization (up to 98 %) was obtained by using chitosan as a carrier. The optimum pH and temperature were not significantly altered by immobilization. High stability of immobilized β-galactosidase during storage was demonstrated. Efficient lactose saccharification (over 90 %) in whey was achieved by using immobilized β-galactosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Moreover, the recent interest in nanotechnology has provided a wealth of diverse nanoscaffolds that support its successful immobilization and improved stabilization on polyurethane powder [22], polyelectrolyte surfaces [23] and Al 2 O 3 nanoparticles [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent interest in nanotechnology has provided a wealth of diverse nanoscaffolds that support its successful immobilization and improved stabilization on polyurethane powder [22], polyelectrolyte surfaces [23] and Al 2 O 3 nanoparticles [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [19] also showed that 1 mM of Mn 2+ lead to decreased β-galactosidase activity in B. longum CCRC 15708. Budriene et al [32] showed that β-galactosidase activity from Penicillium canescens was not sensitive to 1 mM of Na + , K + , Cu 2+ , Fe 2+ , Mn 2+ , and Mg 2+ ions in the growth culture.…”
Section: Induction Of β-Galactosidase By Different Metal Ionsmentioning
confidence: 98%
“…Chitosan was activated with glutaraldehyde following a methodology adapted from Budriene et al [39]. The process was carried out by adding 5% (v/v) glutaraldehyde to 10 g of chitosan gel (10% w/v) at room temperature and pH 7.0 (phosphate buffer 100 mM).…”
Section: Chitosan-glutaraldehyde Activationmentioning
confidence: 99%